1984
DOI: 10.1210/endo-114-4-1426
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Centralα1- andα2-Adrenoceptors in the Regulation of Vasopressin Release and the Cardiovascular System*

Abstract: In order to investigate the role of central alpha 1- and alpha 2-adrenoceptors in the control of vasopressin (ADH) release and the cardiovascular system, norepinephrine (NE) (1.4 microgram/kg), methoxamine (1.4 microgram/kg), yohimbine (60 micrograms/kg), and prazosin (40 micrograms/kg) were administered via the cerebral ventricles in urethane-chloralose-anesthetized dogs after morphine sedation (n = 42). In the control study 0.9% saline was administered. NE resulted in a significant fall in blood pressure, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 0 publications
2
16
1
Order By: Relevance
“…Numerous experiments in a variety of animal models have ascribed both stimulatory and inhibitory roles to the a-1 and a-2 adrenoceptors located on the AVP secreting neurons of the hypothalamus (3,5,6,(12)(13)(14). It is possible that the differences between these studies and ours could be from the basis of interspecies variation as well as from a difference in the developmental stage of the subjects.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Numerous experiments in a variety of animal models have ascribed both stimulatory and inhibitory roles to the a-1 and a-2 adrenoceptors located on the AVP secreting neurons of the hypothalamus (3,5,6,(12)(13)(14). It is possible that the differences between these studies and ours could be from the basis of interspecies variation as well as from a difference in the developmental stage of the subjects.…”
Section: Discussionmentioning
confidence: 80%
“…In addition to the a-1 adrenergic system, other receptors have been shown to be involved (5,6). The rapid changes occurring in AVP-related mechanisms in the nearterm fetus raise important questions about the development of this system.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the hypotensive and bradycardic actions of L-dopa are mediated by stimulation of central a 2 -adrenergic receptors, and again, this conclusion is consistent with previous reports. 6 -21 " 23 The decreases in blood pressure and heart rate produced by L-dopa are thought to result from a reduction in sympathetic neural activity and an increase in cardiac vagal activity.…”
Section: Inhibition Of Vasopressin Secretion By L-dopa/fo/rf Et Almentioning
confidence: 99%
“…5 " 9 Although there is general agreement that central catecholamines are involved in the control of vasopressin release, there is still controversy concerning the nature of this control. Many investigators have concluded that brain catecholamines act to inhibit vasopressin release, 6 ' '• 10~15 while others have presented evidence for a stimulatory effect. 8 ' l6~18 In addition, the relative importance of dopamine and norepinephrine is not clear.…”
mentioning
confidence: 99%
“…NE can increase the central and peripheral release of neuropeptides mainly via the involvement of HA-ergic neurons [67]. Nevertheless, NE has also been reported to inhibit AVP release [71][72][73]. Correlative roles of AVP and 5-HT [31] and/or NE [56] in various aspects of emotional or social behavior or the related disorders have likewise been described.…”
Section: Discussionmentioning
confidence: 99%